2019
DOI: 10.1053/j.ajkd.2018.12.024
|View full text |Cite|
|
Sign up to set email alerts
|

Fasting Urinary Osmolality, CKD Progression, and Mortality: A Prospective Observational Study

Abstract: Rationale & Objective. Chronic kidney disease (CKD) characterized by decreased glomerular filtration rate (GFR) is often accompanied by various degrees of impaired tubular function in the cortex and medulla. Assessment of tubular function may, therefore, be useful in establishing the severity of kidney disease and in identifying those at greater risk of CKD progression. We explored reductions in urinary concentrating ability, a well-known feature of CKD, as a risk factor for GFR decline and end-stage kidney di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Elevated levels of vasopressin have been reported in individuals with confirmed nephrogenic diabetes insipidus associated with lithium (24). This feature of near normal urine concentrating ability and elevated vasopressin or copeptin (the surrogate marker of vasopressin) levels has been reported in other conditions such as polycystic kidney disease (PKD) (25,26), and during chronic kidney disease (27), during which a decrease in urine concentrating ability is predictive of a steeper decline in mGFR and of ESKD (28). As it is known to play an important role in the pathophysiology of cyst growth in PKD and some authors suggest a deleterious role in CKD as well (29,30), one could hypothesize that it might also be an important mediator of lithium-induced tubulo-interstitial and microcystic kidney disease.…”
Section: Discussionmentioning
confidence: 57%
“…Elevated levels of vasopressin have been reported in individuals with confirmed nephrogenic diabetes insipidus associated with lithium (24). This feature of near normal urine concentrating ability and elevated vasopressin or copeptin (the surrogate marker of vasopressin) levels has been reported in other conditions such as polycystic kidney disease (PKD) (25,26), and during chronic kidney disease (27), during which a decrease in urine concentrating ability is predictive of a steeper decline in mGFR and of ESKD (28). As it is known to play an important role in the pathophysiology of cyst growth in PKD and some authors suggest a deleterious role in CKD as well (29,30), one could hypothesize that it might also be an important mediator of lithium-induced tubulo-interstitial and microcystic kidney disease.…”
Section: Discussionmentioning
confidence: 57%
“…in 2003 demonstrated low urine osmolality is an independent risk factor for reduced kidney function regardless of polycystic kidney disease (PKD) [ 11 ]. Recently, two prospective studies using urine osmolality tertiles, conducted in 2019 by the French NephroTest Study Group [ 12 ] ( N = 2,084; mean age 58.7 ± 15.2 years; 67.7% male; mean urine osmolality 502.7 ± 151.7 mOsm/kg; median baseline GFR 40.2 mL/min/1.73m 2 with interquartile range of 29.1–54.5) and Lee et al from the Korean Cohort Study on the Outcome of Chronic Kidney Disease Patients (KNOW-CKD) [ 13 ] ( N = 1,999; mean age 53.8 ± 12.1 years; 61% males; mean baseline eGFR 50.3 ± 30.0 mL/min/1.73m 2 ) demonstrated that low urine osmolality was associated with a higher risk of kidney impairment and there was a significant interaction between urine osmolality and eGFR. These are consistent with the findings in our subgroup with eGFR < 60 mL/min/1.73m 2 ( N = 172, 2.3%; mean age 59.5 ± 0.6 years; 45.6% male; mean urine osmolality 559.2 ± 21.8 mOsm/kg; mean eGFR 52.0 ± 0.6 mL/min/1.73m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 6 hours after LT, osmolality predicted 60-day mortality with a median of 354 in the survivor group vs 534 in the non-survivor group with a p 0,004 and an AUC 0,21 (CI 0,07-0,34). The multicentre study reported by Tabzadeh et al with 2084 patients concluded that osmolality, in addition to GFR and albuminuria, is a useful tool for assessing non-glomerular damage in patients with CKD 18 .…”
Section: Discussionmentioning
confidence: 99%